EFFECT OF EMPLOYEE RETENTION FACTORS ON ORGANIZATIONAL COMMITMENT - Putra, Ali Syah; eddy, Eddy; Afriani, Diana; Gurning, Lenny; Hutabarat, Gloria Cahaya Julida (AGUSPATI Research Institute, 2021)
It is necessary to retain talented employees familiar with the working conditions and perform better than the new employees. Most employers usually attempt to decrease employee turnover to decrease training costs, recruitment costs, loss of talent and organizational knowledge. P.T. Alfa Scorpii is an automotive shop which is located at Jl. Adam Malik no 34 Medan. Based on the information that the writer has research, there is a turnover among the employees, and the employer struggles to retain their valuable employees. The employees are not committed to the organization and decided to leave the organization for another job due to compensation, job characteristics, training and development opportunities, supervisor support, career opportunities, and work/life policies. The writer used employees in the sales department in P.T. Alfa Scorpii Medan as the population. The sampling theory by Slovin is 95 people. The sampling technique used is the simple random sampling in which each member of the population has an equal and known chance of being selected In analyzing data, the writer used some methods such as statistics, validity test, reliability test, correlation test, determination test, linear regression, and hypothesis test. According to the result calculation data through the respondents' answers, the writer got the result of 0.82, which means retention factors positively and significantly affect organizational commitment at P.T. Alfa Scorpii Medan. From the calculation of the hypothesis test, zcount= 6.83. The zcount > ztable (6.83>1.96) means the Null Hypothesis (Ho) is rejected, and the Alternative Hypothesis (Ha) is accepted. Retention factors affect organizational commitment at P.T. Alfa Scorpii Medan. Keywords: Retention Factors, Organizational Commitment